2012
DOI: 10.1017/s0007114512001407
|View full text |Cite
|
Sign up to set email alerts
|

Baker's yeast β-glucan supplementation increases monocytes and cytokines post-exercise: implications for infection risk?

Abstract: Strenuous aerobic exercise is known to weaken the immune system, and while many nutritional supplements have been proposed to boost post-exercise immunity, few are known to be effective. The purpose of the present study was to evaluate whether 10 d of supplementation with a defined source of baker's yeast b-glucan (BG, Wellmune WGP w ) could minimise post-exercise immunosuppression. Recreationally active men and women (n 60) completed two 10 d trial conditions using a cross-over design with a 7 d washout perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 29 publications
9
50
0
1
Order By: Relevance
“…Blood analysis showed that ingestion of β-glucans significantly increases the total number of monocytes as well as of pro-inflammatory monocytes (p < 0.05). Further ex vivo LPS stimulation significantly increased plasma cytokine production of IL-2, Il-4, IL-5, and interferon-gamma [46]. …”
Section: Studies Performed With the Proprietary Yeast β-Glucan Preparmentioning
confidence: 99%
“…Blood analysis showed that ingestion of β-glucans significantly increases the total number of monocytes as well as of pro-inflammatory monocytes (p < 0.05). Further ex vivo LPS stimulation significantly increased plasma cytokine production of IL-2, Il-4, IL-5, and interferon-gamma [46]. …”
Section: Studies Performed With the Proprietary Yeast β-Glucan Preparmentioning
confidence: 99%
“…The ability of insoluble beta-glucan particulates to prime the immune system is the basis for development of a variety of fungal and yeast-based functional foods that are currently marketed for food use (GRN 239,309,413). For example, the consumption of baker's yeast beta-glucan has been reported to minimize postexercise immunosuppression, and may decrease the severity and the duration of upper respiratory tract infections (Fuller et al, 2012;Carpenter et al, 2013). Similar to beta-1,3-glucans originating from fungal/yeast sources, paramylon also appears to have immune priming properties (Kankkunen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…En un estudio en doble ciego y controlado por placebo realizado en 24 pacientes con rinitis alérgica, el uso de β-glucanos por 12 semanas disminuyó las concentraciones de IL-4 e IL-5 en el fluido nasal sin cambios en el grupo placebo (59). El suplemento de β-glucanos por 10 días durante y post ejercicio aumentó el potencial de los leucocitos sanguíneos para producir IL-2, IL-4, IL-5 e IFN-γ, sugiriendo que los β-glucanos son capaces de modular la inmunidad después del ejercicio (60). Sólo un estudio realizado con ratones Balb/c comparó los 2 tipos de β-glucanos PGG y WGP.…”
unclassified